Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-83 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
The SCI patient Nefeli during exercising only with the legs while playing/working with the iPhone (A) or singing and moving (B). While playing a bit crazy during CDT (B) is beneficial for repair because it keeps the patient in a good mood in spite of the SCI. Being addicted to the iPhone (A) is mostly not beneficial for repair.